Environmental Protection for Sale: Strategic Green Industrial Policy and Climate Finance - Carolyn Fischer (Fondazione Eni Enrico Mattei (FEEM), 2016)
Industrial policy has long been criticized as subject to protectionist interests; accordingly, subsidies to domestic producers face disciplines under World Trade Organization agreements, without exceptions for environmental purposes. Now green industrial policy is gaining popularity as governments search for low-carbon solutions that also provide jobs at home. The strategic trade literature has largely ignored the issue of market failures related to green goods. I consider the market for a new environmental good (like low-carbon technology) whose downstream consumption provides external benefits (like reduced emissions). Governments may have some preference for supporting domestic production, such as by interest-group lobbying, introducing a political distortion in their objective function. I examine the national incentives and global rationales for offering production (upstream) and deployment (downstream) subsidies in producer countries, allowing that some of the downstream market may lie in nonregulating third-party countries. Restraints on upstream subsidies erode global welfare when environmental externalities are large enough relative to political distortions. Climate finance is an effective alternative if political distortions are large and governments do not undervalue carbon costs. Numerical simulations of the case of renewable energy indicate that a modest social cost of carbon can imply benefits from allowing upstream subsidies.
Keywords: F13; F18; H21; Q5; 330; Green Industrial Policy; Emissions Leakage; Externalities; International Trade; Renewable Energy; Subsidies